Analysis of expression, epigenetic, and genetic changes of HNF1B in 130 kidney tumours - Bártů, Michaela; Hojný, Jan; Hájková, Nikola; Michálková, Romana; Krkavcová, Eva; Hadravský, Ladislav; Kleissnerová, Lenka; Bui, Quang Hiep; Stružinská, Ivana; Němejcová, Kristýna; Čapoun, Otakar; Šlemendová, Monika; et al. (Scientific reports, 2020)
Hepatocyte nuclear factor 1 beta (HNF1B) is a transcription factor which plays a crucial role in nephronogenesis, and its germline mutations have been associated with kidney developmental disorders. However, the effects of HNF1B somatic exonic mutations and its role in the pathogenesis of kidney tumours has not yet been elucidated. Depending on the type of the tumour HNF1B may act as a tumour suppressor or oncogene, although the exact mechanism by which HNF1B participates in the process of cancerogenesis is unknown. Using an immunohistochemical approach, and methylation and mutation analysis, we have investigated the expression, epigenetic, and genetic changes of HNF1B in 130 cases of renal tumours (121 renal cell carcinomas, 9 oncocytomas). In the subset of clear cell renal cell carcinoma (ccRCC), decreased HNF1B expression was associated with a higher tumour grade and higher T stage. The mutation analysis revealed no mutations in the analysed samples. Promoter methylation was detected in two ccRCCs and one oncocytoma. The results of our work on a limited sample set suggest that while in papillary renal cell carcinoma HNF1B functions as an oncogene, in ccRCC and chRCC it may act in a tumour suppressive fashion.
Keywords: zárodečné mutace; Kidney; Germ-Line Mutation; epigenomika; Epigenomics; mutační analýza DNA; lidé; karcinom z renálních buněk; DNA Mutational Analysis; hepatocytární jaderný faktor 1-beta; Kidney Neoplasms; Carcinoma, Renal Cell; epigeneze genetická; Hepatocyte Nuclear Factor 1-beta; nádory ledvin; promotorové oblasti (genetika); Promoter Regions, Genetic; ledviny; Epigenesis, Genetic; Humans